"Bittersweet Harvest:The Bracero Program 1942-1964" Exhibition at Broome Library - Broome Library
Image of the Smithsonian and CSU Channel Islands joint exhibition "Bittersweet Harvest: The Bracero Program 1942-1964" at the Broome Library running August-October 2010.